TPACK Practice in Indonesia: Implementation, Learning Outcome, and TPACK Literacy - Adelya, Deana; Ammade, Salasiah; Maming, Khadijah (Magister Pendidikan Bahasa Inggris Universitas Jambi, 2025)
This study investigates the practice of Technological Pedagogical Content Knowledge (TPACK) in Indonesia, focusing on three key dimensions: implementation, learning outcomes, and teacher literacy. In response to the evolving demands of 21st-century education, this research aims to explore how Indonesian educators integrate technology within pedagogical and content frameworks. Using a qualitative literature review method, the study analyzed 53 scholarly articles published between 2016 and 2024. The findings suggest that TPACK implementation in Indonesia shows growing trends, particularly in the contexts of online and blended learning. Teachers who effectively applied TPACK strategies reported improved student engagement, motivation, and academic performance. However, several challenges remain, including limited access to digital infrastructure, inconsistent professional training, and varying levels of TPACK literacy among educators. The study highlights that while the framework holds promise, its sustainable application requires systemic support through policy, training, and institutional readiness. These insights contribute to the discourse on digital pedagogy in developing contexts and emphasize the importance of enhancing teacher competencies to align with future education demands.